Directed content analysis : exploring the readability of forensic scientists' written reports for police, lawyers and judges - Howes, Loene M. (SAGE research methods. Cases, 2014)
This case study describes the process of developing a method to explore the readability of forensic scientists' reports. Content analysis offered a good fit to answering questions about the nature of written communication from scientists to non-scientists. However, specific issues for doing content analysis include deciding upon the criteria to assess and how to assess them.
Keywords: Forensic sciences : Research : Case studies; Readability (Literary style) : Research : Case studies; Content analysis (Communication) : Case studies; Forensic sciences : Research : Case studies; Readability (Literary style) : Research : Case studies